The Relationship between Science and Mathematics Student Learning Outcomes - Dori Lukman Hakim (Postgraduate, University of Mataram, 2023)
This article discusses the relationship between mathematics learning outcomes and natural science learning outcomes at East Teluk Jambe 1 Public Middle School in 227 students from nine classes at the end of the odd semester of the 2022/2023 Academic Year. The relationship between these two subjects can be seen from the results of mathematics learning scores and science learning scores by looking at the relationship that occurs based on student ability categories, namely the High Mathematics Category (HMC) and the Low Mathematics Category (LMC), the High Science Category (HSC), the Low Science Category (LSC) is then also seen based on the overall value of mathematics and science. The statistical test used is a correlation test to see each relationship. The results obtained the overall value of mathematics learning outcomes will have a sufficient influence on the overall value of science learning outcomes and vice versa, the effect of a sufficient relationship in the value of mathematics learning outcomes on science or vice versa occurs when students' learning abilities in mathematics or science are high. The overall mathematics learning result is 83.20 while the average science learning result is 85.63, and the science score is higher than the math score. Students who study mathematics will have an influence on learning science, and vice versa students who study mathematics will have an influence on learning mathematics so that these two subjects must be given to students